The effects of policy discourse on the governance of deforestation and forest degradation reduction in the Democratic Republic of Congo (DRC) - Majambu, E.; Tsayem Demaze, M.; Sufo-Kankeu, R.; Sonwa, D.J.; Ongolo, S. (Wiley, 2024)
The international initiative to combat deforestation and forest degradation, known as REDD+, was put on the DRC agenda following actors' policy discourse aimed at convincing policy-makers of its effectiveness. This paper uses discursive institutionalism (DI) as a theoretical and analytical framework to analyse a set of selected policy documents on REDD+ issue and to assess the effects of policy discourse on deforestation reduction governance in DRC. From an empirical standpoint, interviews with key actors involved in the DRC REDD+ processes and field observations show that four main types of discourse accompanied the adoption of REDD+ in the DRC: a discourse promoting REDD+ through its forest conservation component, as a policy instrument that would bring in significant financial resources to the DRC forest-related state bureaucracies, a discourse that considers REDD+ as an efficient mean of reducing poverty while promoting sustainability through “green development”, a discourse presenting REDD+ as a way of reducing marginalisation of local communities and indigenous peoples by recognising their customary rights, and finally, a discourse promoting REDD+ as a tool for territorial planning and governance. In addition, the paper points out strong links between DRC REDD+ policy discourse and three types of governance approaches: organisational and fiduciary governance, territorial governance, local development and benefit sharing governance. Our analysis also shows that political discourse has played a significant role in the adoption of substantial policies aimed at reducing deforestation in DRC.